Gedanken zum jüdischen Offenbarungsverständnis Biblische und nachbiblische Perspektiven - Gesundheit, Shimon 1961- (2018)
The path from the earliest description of the theophany on Mount Sinai in the book Exodus to early rabbinical creativity in the interpretation of revelation can be described as a hermeneutical process of increasing rationality.
Keywords: Deuteronomius; Exodus; Offenbarung; Sinai; Talmud; Theophanie; Tora; frührabbinisches Judentum